Preparation method of large-granularity cobaltosic oxide for battery

By using sodium oxalate and ammonium niobium oxalate in the positive electrode material of lithium-ion battery for coprecipitation reaction, combined with freeze-drying and high-temperature roasting technology, high-performance, large-particle cobalt tetoxide was prepared, which solved the insufficient performance of the preparation of large-particle cobalt tetoxide in the prior art. The problem is that the cycle stability and processing performance of lithium-ion batteries have been significantly improved.

CN119461498AActive Publication Date: 2025-02-18YANGJIANG FEDERAL METAL CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411714086.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

It is difficult to effectively prepare high-performance, large-particle cobalt tetroxide in the prior art, which affects the cycle stability and processing performance of lithium-ion batteries.

Method used

The cobalt salt was dissolved in deionized water, mixed with sodium oxalate and ammonium niobium oxalate, and carried out coprecipitation reaction, followed by freeze-drying and high-temperature calcination, and finally mixed with glycine and then roasted to prepare large-grain cobalt tetroxide.

Benefits of technology

High cycle stability and optimized performance of large-particle cobalt tetroxide are achieved, and the energy density, cycle stability and processing performance of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of large-granularity cobaltosic oxide for a battery, and belongs to the technical field of battery preparation. The preparation method comprises the following steps: dissolving cobalt salt in deionized water to obtain a high-concentration cobalt ion solution, mixing sodium oxalate and niobium ammonium oxalate for use to form a specific precursor structure, carrying out a co-precipitation reaction on cobalt ions, oxalate and niobium ammonium oxalate in an aqueous solution to generate a cobalt-containing oxalate and niobate compound precipitate, and carrying out solid-liquid separation on the cobalt-containing oxalate and niobate compound precipitate. Then hydrogen peroxide is used for promoting oxidation of cobalt ions, and formation and crystallization of cobalt oxalate precipitates are further promoted; in the preparation process, water is effectively removed through freeze drying, meanwhile, the morphology and structure of precipitates are kept, organic matter and volatile impurities are removed in the roasting and re-roasting process, and formation and stability of a cobaltosic oxide crystal structure are promoted; the stable crystal structure is favorable for prolonging the cycle life and improving the safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery preparation, and relates to a method for preparing large-particle cobalt tetroxide for batteries. Background Art

[0002] As one of the most widely used secondary batteries, the performance improvement of lithium-ion batteries has always been a hot topic of research. The cathode material is one of the key factors in the performance of lithium-ion batteries, and the optimization of the performance of cobalt tetroxide, as an important cathode material precursor, is of great significance for improving the energy density, cycle stability and safety of lithium-ion batteries.

[0003] In lithium-ion batteries, the particle size of the cathode material directly affects the performance of the battery. Generally speaking, smaller particle sizes can provide higher specific surface area and shorter ion diffusion paths, which are conducive to the rapid deintercalation of lithium ions and the high rate performance of the battery. However, in some cases, such as improving the cycle stability and processing performance of the battery, large-particle cathode materials may be more advantageous. Large-particle cobalt tetroxide can improve the processing performance and cycle stability of the material while ensuring battery performance by optimizing the particle size distribution and morphology. With the development of electric vehicles, energy storage systems and other fields, the performance requirements for lithium-ion batteries are getting higher and higher. As an important precursor of cathode materials, large-particle cobalt tetroxide has significant advantages in improving battery performance.

[0004] As an important component of lithium battery positive electrode materials, large-particle cobalt tetroxide can improve the cycle stability of the battery. Therefore, how to prepare high-performance large-particle cobalt tetroxide has become a hot topic. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing large-particle cobalt tetroxide for battery, wherein the cobalt tetroxide prepared by the method has the characteristic of high cycle stability.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing large-particle cobalt tetroxide for batteries, the specific process of the large-particle cobalt tetroxide preparation method is as follows:

[0008] S1: dissolving a cobalt salt in deionized water to obtain a cobalt ion solution A having a mass fraction of 30 to 50%;

[0009] S2: Sodium oxalate and ammonium niobium oxalate are mixed in a mass ratio of 1:(0.5-3), and dispersed in deionized water to obtain a mixed solution B with a mass fraction of 10%;

[0010] S3: Add cobalt ion solution A dropwise into mixed solution B in a volume ratio of 2:1, stir at a speed of 150 r / min while dropping, and heat to 50°C for 2 to 3 hours, then add 1 wt% hydrogen peroxide solution with a mass fraction of 10%, slowly heat to 65°C at a rate of 2°C / min, continue stirring for 0.5 to 1 hour, and obtain mixed solution C;

[0011] S4: freezing the mixed solution C in liquid nitrogen for 15 min, and then drying it at -50°C in a nitrogen atmosphere for 6 h to obtain a mixture D;

[0012] S5: Transfer the mixture D to a muffle furnace, heat it from room temperature to 500-600° C., and calcine it for 3 hours. After the calcination is completed, introduce nitrogen gas to purge it, and cool it to room temperature to obtain a mixture E;

[0013] S6: Mix the mixture E and glycine in a mass ratio of 4:1, grind at a speed of 300 r / min for 0.5 h, and then place the mixture in a muffle furnace preheated to 200° C. and burn for 10 to 20 min, then slowly heat up to 600° C. and continue roasting for 2 h. After roasting, use nitrogen to purge and quickly cool to room temperature, and crush to obtain the large-particle cobalt tetroxide.

[0014] Furthermore, the cobalt salt in S1 is one or more of cobalt sulfate, cobalt chloride, and cobalt nitrate.

[0015] Further, the cobalt ion solution A in S3 is added dropwise into the mixed solution B at a rate of 3 s / drop.

[0016] Furthermore, the heating rate in S5 is 10°C / min.

[0017] Furthermore, the purge flow rate of nitrogen in S5 is 10 m / s.

[0018] Furthermore, the rate of slow heating in S6 is 3°C / min.

[0019] Furthermore, the flow rate of the nitrogen purge in S6 is 20 m / s.

[0020] Furthermore, the large-particle cobalt oxide prepared in S6 has a particle size of 20 to 25 μm.

[0021] The present invention first dissolves cobalt salt in deionized water to obtain a high-concentration cobalt ion solution A, which provides sufficient cobalt sources for subsequent reactions. The use of deionized water can avoid the introduction of impurity ions and improve the purity of the product. The mixed use of sodium oxalate and ammonium niobium oxalate helps to form a specific precursor structure, thereby affecting the morphology and particle size of the final product. Cobalt ions react with oxalate and ammonium niobium oxalate in an aqueous solution to generate a complex precipitate of oxalate and niobate containing cobalt. After sodium oxalate and ammonium niobium oxalate are dissolved in water, oxalate ions can react with cobalt ions to form a cobalt-containing precipitate.

[0022] Sodium oxalate is used as a precipitant to react with cobalt ions to form cobalt oxalate precipitate. This step is key to the formation of cobalt tetroxide precursors, as it ensures that cobalt ions can be precipitated from the solution in a controlled manner, providing a good starting material for the subsequent high-temperature calcination process.

[0023] Ammonium niobium oxalate not only provides oxalate ions to participate in the precipitation reaction, but more importantly, introduces the element niobium. The introduction of niobium has a significant effect on the properties and crystal structure of cobalt tetroxide. The addition of ammonium niobium oxalate changes the kinetic and thermodynamic conditions of the precipitation reaction, thereby affecting the formation and growth process of cobalt oxalate precipitation.

[0024] Niobium is a metal element with special properties. Its introduction can significantly change the crystal structure and properties of cobalt tetroxide. When niobium enters the lattice of cobalt tetroxide, it will cause lattice distortion. This distortion will reduce the grain boundary energy, so that the energy barrier that the grain needs to overcome during the growth process is reduced, thereby promoting the growth of the grains; niobium exists in cobalt tetroxide in the form of solid solution, forming solid solution strengthening to improve the strength and stability of the grains, and is also conducive to the growth of the grains; in the precipitation reaction process, niobium can also act as a nucleation center or promoter to promote the formation and growth of cobalt oxalate nuclei. These nuclei further grow into cobalt tetroxide grains during the subsequent high-temperature roasting process. Therefore, niobium doping will promote the growth of cobalt tetroxide grains, thereby helping to form large-grained products. In addition, niobium doping can also improve the conductivity, stability and other properties of cobalt tetroxide. Niobium can improve its conductivity by changing the band structure or carrier concentration of cobalt tetroxide. Specifically, the introduction of niobium may form new energy levels or impurity energy levels, making it easier for electrons or holes to migrate in the crystal lattice; niobium also reduces the probability of electron scattering at grain boundaries by promoting grain growth and reducing grain boundaries, thereby improving conductivity. Due to the strong interaction between niobium and cobalt, they may form stable chemical bonds or structural units, allowing cobalt tetroxide to maintain good structural stability during the electrochemical cycle; the introduction of niobium also improves cobalt tetroxide's tolerance to ions in the electrolyte, reduces the destructive effect on the crystal lattice during ion insertion / extraction, and thus improves the battery's cycle stability, which is very important for battery applications.

[0025] Hydrogen peroxide is a strong oxidant that can participate in chemical reactions and oxidize substances to a higher valence state. In this preparation process, hydrogen peroxide can promote the oxidation of cobalt ions and help form a more stable cobalt compound precursor. The addition of hydrogen peroxide changes the redox potential of the reaction system, which helps to further promote the formation and crystallization of cobalt oxalate precipitation. Good crystallinity is essential for the preparation of large-particle, high-purity cobalt tetroxide.

[0026] Freeze drying can effectively remove moisture while maintaining the morphology and structure of the precipitate; drying under a nitrogen atmosphere can prevent oxidation and protect the chemical properties of the product.

[0027] The roasting process helps remove organic and volatile impurities while promoting the transformation of the precursor to cobalt oxide. Glycine, as a fuel, burns at high temperatures to produce a large amount of gas, which helps to form a porous structure and promotes the formation of large particle size. The re-roasting process further consolidates the crystal structure of cobalt oxide and improves the purity and stability of the product. The roasting and re-roasting process not only removes organic and volatile impurities, but also promotes the formation and stabilization of the cobalt oxide crystal structure. This stable crystal structure helps to improve the cycle life and safety of the battery.

[0028] Beneficial effects of the present invention:

[0029] In the preparation process of the present invention, sodium oxalate and ammonium niobium oxalate are mixed and used, which not only realizes the effective precipitation of cobalt ions, but also optimizes the performance of cobalt tetroxide by introducing niobium elements;

[0030] The invention removes organic matter and volatile impurities through the roasting and re-roasting processes, and also promotes the formation and stabilization of the cobalt tetroxide crystal structure. The stable crystal structure is helpful to improve the cycle life and safety of the battery. DETAILED DESCRIPTION

[0031] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0032] Example 1

[0033] S1: dissolving cobalt sulfate in deionized water to obtain a cobalt ion solution A with a mass fraction of 40%;

[0034] S2: Sodium oxalate and ammonium niobium oxalate are mixed in a mass ratio of 1:2, dispersed in deionized water, and a mixed solution B with a mass fraction of 10% is obtained;

[0035] S3: Add cobalt ion solution A to mixed solution B at a rate of 3s / drop, with a volume ratio of 2:1. Stir at a speed of 150r / min while adding, and heat to 50°C for 2.5h. Then add 1wt% 10% hydrogen peroxide solution, slowly heat to 65°C at a rate of 2°C / min, and continue stirring for 0.5h to obtain mixed solution C.

[0036] S4: freezing the mixed solution C in liquid nitrogen for 15 min, and then drying it at -50°C in a nitrogen atmosphere for 6 h to obtain a mixture D;

[0037] S5: Transfer the mixture D to a muffle furnace, heat it from room temperature to 500°C at a heating rate of 10°C / min, and calcine for 3 hours. After calcination, introduce nitrogen gas for purging at a nitrogen purging rate of 10 m / s, and cool it to room temperature to obtain a mixture E.

[0038] S6: Mix the mixture E and glycine in a mass ratio of 4:1, grind at a speed of 300 r / min for 0.5 h, and then place the mixture in a muffle furnace preheated to 200°C and burn for 15 min, then slowly heat it to 600°C and continue roasting for 2 h, the rate of slow heating is 3°C / min, and after roasting, use nitrogen purge to quickly cool to room temperature, the flow rate of nitrogen purge is 20 m / s, and crush to obtain the large-particle cobalt tetroxide with a particle size of 20 to 25 μm.

[0039] Example 2

[0040] S1: dissolving cobalt chloride in deionized water to obtain a cobalt ion solution A with a mass fraction of 30%;

[0041] S2: Sodium oxalate and ammonium niobium oxalate are mixed in a mass ratio of 1:0.5, dispersed in deionized water, and a mixed solution B with a mass fraction of 10% is obtained;

[0042] S3: Add cobalt ion solution A to mixed solution B at a rate of 3s / drop, with a volume ratio of 2:1. Stir at a speed of 150r / min while adding, and heat to 50°C for 2h. Then add 1wt% 10% hydrogen peroxide solution, slowly heat to 65°C at a rate of 2°C / min, and continue stirring for 0.5h to obtain mixed solution C.

[0043] S4: freezing the mixed solution C in liquid nitrogen for 15 min, and then drying it at -50°C in a nitrogen atmosphere for 6 h to obtain a mixture D;

[0044] S5: Transfer the mixture D to a muffle furnace, heat it from room temperature to 500°C at a heating rate of 10°C / min, and calcine for 3 hours. After calcination, introduce nitrogen gas for purging at a nitrogen purging rate of 10 m / s, and cool it to room temperature to obtain a mixture E.

[0045] S6: Mix the mixture E and glycine in a mass ratio of 4:1, grind at a speed of 300 r / min for 0.5 h, and then place the mixture in a muffle furnace preheated to 200°C and burn for 20 min, then slowly heat it to 600°C and continue roasting for 2 h, the rate of slow heating is 3°C / min, and after roasting, use nitrogen purge to quickly cool to room temperature, the flow rate of nitrogen purge is 20 m / s, and crush to obtain the large-particle cobalt tetroxide with a particle size of 20 to 25 μm.

[0046] Example 3

[0047] S1: dissolving cobalt nitrate in deionized water to obtain a cobalt ion solution A with a mass fraction of 50%;

[0048] S2: Sodium oxalate and ammonium niobium oxalate are mixed in a mass ratio of 1:3, dispersed in deionized water, and a mixed solution B with a mass fraction of 10% is obtained;

[0049] S3: Add cobalt ion solution A to mixed solution B at a rate of 3s / drop, with a volume ratio of 2:1. Stir at a speed of 150r / min while adding, and heat to 50°C for 3h. Then add 1wt% 10% hydrogen peroxide solution, slowly heat to 65°C at a rate of 2°C / min, and continue stirring for 1h to obtain mixed solution C.

[0050] S4: freezing the mixed solution C in liquid nitrogen for 15 min, and then drying it at -50°C in a nitrogen atmosphere for 6 h to obtain a mixture D;

[0051] S5: Transfer the mixture D to a muffle furnace, heat it from room temperature to 600°C at a heating rate of 10°C / min, and calcine for 3 hours. After calcination, introduce nitrogen purge at a nitrogen purge flow rate of 10 m / s, and cool it to room temperature to obtain a mixture E.

[0052] S6: Mix the mixture E and glycine in a mass ratio of 4:1, grind at a speed of 300 r / min for 0.5 h, and then place the mixture in a muffle furnace preheated to 200°C and burn for 10 min, then slowly heat it to 600°C and continue roasting for 2 h, the rate of slow heating is 3°C / min, and after roasting, use nitrogen purge to quickly cool to room temperature, the flow rate of nitrogen purge is 20 m / s, and crush to obtain the large-particle cobalt tetroxide with a particle size of 20 to 25 μm.

[0053] Comparative Example 1

[0054] In this comparative example, no ammonium niobium oxalate was added during the preparation process, and the remaining steps were consistent with those of Example 1.

[0055] Comparative Example 2

[0056] In this comparative example, no hydrogen peroxide was added during the preparation process, and the remaining steps were consistent with those in Example 1.

[0057] Comparative Example 3

[0058] In this comparative example, S6 is not re-calcined during the preparation process, and the remaining steps are consistent with Example 1.

[0059] Comparative Example 4

[0060] In this comparative example, the calcination operation of S5 is not performed during the preparation process, and the remaining steps are consistent with those of Example 1.

[0061] The embodiments and comparative examples were tested for performance.

[0062] The cycle retention rate test was carried out according to the standard GB / T 23366-2009. The experimental results are summarized in the following table:

[0063] 200 cycles retention rate (%) Example 1 85 Example 2 83 Example 3 83 Comparative Example 1 70 Comparative Example 2 76 Comparative Example 3 74 Comparative Example 4 75

[0064] It can be seen from the data of the examples and comparative examples that the addition of ammonium niobium oxalate and hydrogen peroxide, as well as the secondary calcination treatment, all make the obtained large-particle cobalt tetroxide have a better cycle life.

[0065] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing large-particle cobalt tetroxide for battery, characterized in that: The specific process of the method for preparing large-particle cobalt tetroxide is as follows: S1: dissolving a cobalt salt in deionized water to obtain a cobalt ion solution A having a mass fraction of 30 to 50%; S2: Sodium oxalate and ammonium niobium oxalate are mixed in a mass ratio of 1:(0.5-3), and dispersed in deionized water to obtain a mixed solution B with a mass fraction of 10%; S3: Add cobalt ion solution A dropwise into mixed solution B in a volume ratio of 2:1, stir at a speed of 150 r / min while dropping, and heat to 50°C for 2 to 3 hours, then add 1 wt% hydrogen peroxide solution with a mass fraction of 10%, slowly heat to 65°C at a rate of 2°C / min, continue stirring for 0.5 to 1 hour, and obtain mixed solution C; S4: freezing the mixed solution C in liquid nitrogen for 15 min, and then drying it at -50°C in a nitrogen atmosphere for 6 h to obtain a mixture D; S5: Transfer the mixture D to a muffle furnace, heat it from room temperature to 500-600° C., and calcine it for 3 hours. After the calcination is completed, introduce nitrogen gas to purge it, and cool it to room temperature to obtain a mixture E; S6: Mix the mixture E and glycine in a mass ratio of 4:1, grind at a speed of 300 r / min for 0.5 h, and then place the mixture in a muffle furnace preheated to 200° C. and burn for 10 to 20 min, then slowly heat up to 600° C. and continue roasting for 2 h. After roasting, use nitrogen to purge and quickly cool to room temperature, and crush to obtain the large-particle cobalt tetroxide.

2. The method for preparing large-particle cobalt tetroxide for battery according to claim 1, characterized in that: The cobalt salt in S1 is one or more of cobalt sulfate, cobalt chloride and cobalt nitrate.

3. The method for preparing large-particle cobalt tetroxide for battery according to claim 1, characterized in that: The cobalt ion solution A in S3 is added dropwise into the mixed solution B at a rate of 3s / drop.

4. The method for preparing large-particle cobalt tetroxide for battery according to claim 1, characterized in that: The heating rate in S5 is 10°C / min.

5. The method for preparing large-particle cobalt tetroxide for battery according to claim 1, characterized in that: The purge flow rate of nitrogen in S5 is 10 m / s.

6. The method for preparing large-particle cobalt tetroxide for battery according to claim 1, characterized in that: The rate of slow heating in S6 is 3°C / min.

7. The method for preparing large-particle cobalt tetroxide for battery according to claim 1, characterized in that: The flow rate of nitrogen purge in S6 is 20 m / s.

8. The method for preparing large-particle cobalt tetroxide for battery according to claim 1, characterized in that: The large-particle cobalt tetroxide prepared in S6 has a particle size of 20 to 25 μm.

Citation Information

Patent Citations

  • Method for preparing large particle size doped tricobalt tetroxide

    CN108298596A

  • Preparation method of niobium, tungsten and tantalum-doped cobalt trioxide

    CN108455686A

  • Method for producing lithium-containing multiple oxide suitable for lithium ion secondary battery

    JP2010070427A

  • Method for producing cobalt hydroxide, method for producing cobalt oxide and method for producing lithium cobaltate

    JP2013170099A

  • Cobalt oxide powder production method

    RU2680514C1